Design and Development of Mini-Compact Wilkinson Power Divider for X-Band Man-Pack Surveillance Radar - Yusnita Rahayu; Lara Putri Utami; Teguh Praludi; Topik Teguh Estu; Yussi Perdana Saputera; Anhar Anhar (Jurnal Elektronika dan Telekomunikasi, 2023)
This paper presents the design and development of a mini-compact Wilkinson Power Divider (WPD) operating at 9.3 GHz, with a wide bandwidth of 200 MHz, for the Man-Pack Surveillance Radar (MPSR) application. The design of the WPD was carried out using Advanced Design System (ADS) software with a microstrip feeding technique. The substrate material used in this design was Duroid Roger 5880, which has a thickness (h) of 1.575 mm, dielectric constant (εr) of 2.20, and loss tangent (tan δ) of 0.0009. A WPD was designed, developed, and measured. The simulation results obtained included return loss (S11) -37.50 dB, (S22) -26.59 dB, (S33) -26.09 dB, insertion loss (S21) -3.61 dB and (S31) - 2.55 dB, and isolation (S32) -12.89 dB. Overall, the simulation result parameters worked at a frequency of 9.3 GHz. Furthermore, when the WPD measurement produces a measured return loss of (S11) -28.69 dB, (S22) -28.5 dB, (S33) -29.95 dB, insertion loss (S21) -6.61 dB, and (S31) -7.55 dB, and isolation (S32) -21.89 dB. The dimensions resulting from the realization were 20.5 mm x 20 mm.